(untitled) (REMUNOM, 2025)
This article analyzes the living will and its (in)effectiveness in the context of Brazilian succession law. The study seeks to understand the extent to which this legal instrument, associated with advance directives, is supported by the national legal system and whether it has practical repercussions in the realm of succession. To this end, the study examines the legal foundations, ethical and regulatory provisions, as well as the different types of wills provided for in the Civil Code of 2002. Using a deductive method based on bibliographic and documentary research, this work investigates the compatibility (or lack thereof) of the living will with the current succession regime, questioning whether it could, in any way, produce legal effects in the field of succession law.